Kajian Hukum terhadap Tindak Pidana Kampanye Hitam di Media Elektronik berdasarkan Perspektif Pemilihan Umum di Indonesia (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the legal regulations on black campaign crimes in electronic media from the perspective of general elections in Indonesia. The research method used is normative juridical with a statutory, case, and conceptual approach. The results of the study indicate that the legal regulations on black campaigns in electronic media in elections in Indonesia are not yet firm and responsive to developments in information technology. Although the Election Law (Law No. 7/2017 in conjunction with Law No. 7/2023) prohibits insults, defamation, and the spread of slander by implementers, participants, and official campaign teams, this provision does not explicitly cover black campaigns by other parties in electronic media. The absence of the phrase